2021
DOI: 10.2109/jcersj2.21005
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric properties of Tb-doped LiF/CaF<sub>2</sub> eutectic composite

Abstract: We have developed a LiF/CaF 2 :Tb eutectic composite as a novel thermoluminescence (TL) dosimetric material. The LiF/CaF 2 :Tb eutectic composite was obtained using a melt-solidification method with a lower melting temperature than that of LiF and CaF 2 . The results of the PL emission and excitation spectra, the X-ray induced radioluminescence decay curve, and the TL emission spectrum indicate that the emissions of LiF/CaF 2 :Tb eutectic composite are due to 4f-4f transitions of the Tb 3+ ion. The integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Thus, we confirmed that the LiF/CaF 2 :Dy eutectic composite can act as the TL dosimetric material in the X-ray dose range from 1 mGy to 10 Gy. Since the lower detection limits of the non-doped, 15) Ce-doped, 16) Eu-doped, [17][18][19] and Tb-doped LiF/CaF 2 eutectic composites 20) are 0.01-1 mGy, that of the LiF/CaF 2 :Dy eutectic composite is not superior. However, we consider that the LiF/CaF 2 :Dy eutectic composite is one of the interesting materials because it is a dual functional material for neutron detection and X-ray dosimetry.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, we confirmed that the LiF/CaF 2 :Dy eutectic composite can act as the TL dosimetric material in the X-ray dose range from 1 mGy to 10 Gy. Since the lower detection limits of the non-doped, 15) Ce-doped, 16) Eu-doped, [17][18][19] and Tb-doped LiF/CaF 2 eutectic composites 20) are 0.01-1 mGy, that of the LiF/CaF 2 :Dy eutectic composite is not superior. However, we consider that the LiF/CaF 2 :Dy eutectic composite is one of the interesting materials because it is a dual functional material for neutron detection and X-ray dosimetry.…”
Section: Resultsmentioning
confidence: 97%
“…We have studied the non-doped, 15) Ce-doped, 16) Eu-doped, [17][18][19] and Tb-doped LiF/CaF 2 eutectics. 20) In the case of LiF/CaF 2 eutectics, LiF can act as a neutron converter and CaF 2 layer can act as a luminescence material. The LiF/CaF 2 eutectic composites can be used for neutron detection.…”
Section: Introductionmentioning
confidence: 99%
“…In the radiation measurements, the composite materials have been studied as storage phosphors and scintillators for neutron detectors. [83][84][85][86][87][88][89] To efficiently readout the OSL signals, it is preferable that the OSL and stimulation were similar to the spectral sensitivity of a photodetector and the wavelength of stimulation light. Figure 4 shows OSL and stimulation spectra of the Eu-doped Cs(Cl x , Br 1-x ) translucent ceramics.…”
Section: Cesium Mixed Halide Translucent Ceramicsmentioning
confidence: 99%
“…Studies on materials for scintillators and dosimetric materials have been intensively performed over the past decades. (2)(3)(4)(5)(6)(12)(13)(14)(15) This area of research is still attractive and recent studies have reported on various types of materials such as single crystals, (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) glasses, (30)(31)(32)(33)(34)(35)(36)(37) sintered ceramics, (38)(39)(40)(41)(42)(43)(44)(45) eutectic composites, (46)(47)(48) organic materials, (49,50) and organic-inorganic hybrid materials. (51,52) Among these materials, glasses are interesting research targets due to the advantages of high formability, transparency, and degree of freedom of composition.…”
Section: Introductionmentioning
confidence: 99%